Public concern about, and desire for research into, the human health effects of marine plastic pollution: Results from a 15-country survey across Europe and Australia. (July 2021) - Davison, Sophie M.C.; White, Mathew P.; Pahl, Sabine; Taylor, Tim; Fielding, Kelly; Roberts, Bethany R.; Economou, Theo; McMeel, Oonagh; Kellett, Paula; Fleming, Lora E.
Highlights: 15-country survey of health-related perceptions of marine plastic pollution. Public extremely concerned over human health impacts of marine plastic pollution. Strong public support for research into marine plastic pollution and human health. Socio-political and personality factors predict public concern and research support. Public concern is positively associated with support for research. Abstract: Marine plastic pollution is caused by humans and has become ubiquitous in the marine environment. Despite the widely acknowledged ecological consequences, the scientific evidence regarding detrimental human health impacts is currently debated, and there is no substantive evidence surrounding public opinion with respect to marine plastic pollution and human health. Results from a 15-country survey (n = 15, 179) found that both the European and Australian public were highly concerned about the potential human health impacts of marine plastic pollution, and strongly supported the funding of research which aims to better understand its health/wellbeing implications. Multi-level modelling revealed that these perceptions varied across socio-demographic factors (e.g. gender), political orientation, marine contact factors (e.g. marine occupation and engagement in coastal recreation activities) and personality traits (e.g. openness, conscientiousness and agreeableness). Quantifying attitudes, as well as understanding how individual-level differences shape risk perception will enable policy makers and communicators to develop more targeted communications and initiatives that target a reduction in marine plastic pollution.